2019
DOI: 10.1111/neup.12594
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PD‐L1 expression and T cell infiltration in different molecular subgroups of diffuse midline gliomas

Abstract: Diffuse midline gliomas (DMGs) are rare and devastating tumors with limited therapeutic options. Programmed death-ligand 1 (PD-L1) expression represents a potential predictive biomarker for immunotherapy. One hundred and twenty-six DMGs (89 adult and 37 pediatric) were assessed for immune profile (PD-L1, cluster of differentiation (CD3, CD8) and genetic markers (mutation in 27th amino acid of histone H3 (H3K27M), alpha thalassemia/mental retardation syndrome X-linked (ATRX), isocitrate dehydrogenase 1 (IDH1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…In CNS malignancies, tumor molecules can avoid detection by recruiting and coordinating T lymphocytes, and transform the immune system from protective to toxic ( 10 ). In spinal cord, the expression rate of PD-L1 is about 20% according to one study ( 11 ). Clinical trials targeting immune checkpoints have been carried out in intracranial gliomas, although the results have not been satisfactory and the study of spinal astrocytomas is still in the blank.…”
Section: Spinal Cord Microenvironment and Its Impact On Tumor Biologymentioning
confidence: 99%
“…In CNS malignancies, tumor molecules can avoid detection by recruiting and coordinating T lymphocytes, and transform the immune system from protective to toxic ( 10 ). In spinal cord, the expression rate of PD-L1 is about 20% according to one study ( 11 ). Clinical trials targeting immune checkpoints have been carried out in intracranial gliomas, although the results have not been satisfactory and the study of spinal astrocytomas is still in the blank.…”
Section: Spinal Cord Microenvironment and Its Impact On Tumor Biologymentioning
confidence: 99%
“…Staining for p53 was graded as 0 if no cells stained; 1 + if 0-10% stained; 2 + if 10-50% stained and 3 + if > 50% stained. Grade 2 + and above was considered positive [21]. For H3K27M expression, intense nuclear staining in more than 80% cells was taken as positive (21).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Grade 2 + and above was considered positive [21]. For H3K27M expression, intense nuclear staining in more than 80% cells was taken as positive (21). For IDH, combined cytoplasmic and nuclear staining was interpreted as immunopositive and for ATRX expression; only nuclear staining was considered for evaluation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Non-related articles, cases, and reviews were excluded. Eight articles were nally identi ed as eligible studies for further assessment [9][10][11][12][13][14][15]22 .…”
Section: Study Selectionmentioning
confidence: 99%
“…Recently, TILs have also gained attentions in the prognosis of gliomas. However, some studies indicated that TILs were good biomarker for gliomas [9][10][11][12][13][14] while some studies revealed that no signi cant correlation was observed between TILs and gliomas 9,10,13,15 . In order to reach an agreement, we systematically reviewed the studies focused on glioma and TILs.…”
Section: Introductionmentioning
confidence: 99%